Note on Beam-Column Moment Amplification Factor - Iwankiw, Nestor R. (Engineering Journal, 1984)
This short note has been prepared to clarify and explainthe theoretical derivation of the expressions shown in Table CI.6.1 of the AISC Specification Commentary.